Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $F(x),G(x)\ge 0$ be decreasing functions on $[0,+\infty)$ and $\displaystyle\lim_{x\to+\infty}x(F(x)+G(x))=0$

(1) Prove that: $\forall\varepsilon>0,\displaystyle\lim_{x\rightarrow+\infty}\displaystyle\int_{\varepsilon}^{+\infty}xF(xt)\cos{t}dt=0$

(2) And have $\displaystyle\lim_{n\to+\infty}\displaystyle\int_{0}^{+\infty}(F(t)-G(t))\cos{\dfrac{t}{n}}dt=0$ prove that: $$\displaystyle\lim_{x\to 0}\displaystyle\int_{0}^{\infty}(F(t)-G(t))\cos{(xt)}dt=0$$

the simple problem you can see.

the simple problem see:http://sms.math.ecnu.edu.cn/contest/university03/mathclass11_answer.pdf

this problem from:http://wenku.baidu.com/view/0ac7ae777fd5360cba1adb69.html

share|improve this question
    
Are you sure everything is correct, without typo? For instance, in (1), the integral is $0$ for every value of $x$? Are you sure it is not a limit? –  1015 Feb 20 '13 at 3:43
    
I've checked your link. You do miss a limit. I'll edit if you don't mind. –  1015 Feb 20 '13 at 3:50
    
Sorry but what does "and have" mean? I think you have to prove the limit in $n$ first, and then deduce the one in $x$. –  1015 Feb 20 '13 at 3:54
    
sorry, I have edit,Thank you –  math110 Feb 20 '13 at 3:54
    
mean this :Let $F(x),G(x)\ge 0$ be decreasing functions on $[0,+\infty)$ and $\displaystyle\lim_{x\to+\infty}x(F(x)+G(x))=0$ and $\displaystyle\lim_{n\to+\infty}\displaystyle\int_{0}^{+\infty}(F(t)-G(t))\cos{\‌​dfrac{t}{n}}dt=0$ prove that: $$\displaystyle\lim_{x\to 0}\displaystyle\int_{0}^{\infty}(F(t)-G(t))\cos{(xt)}dt=0$$ –  math110 Feb 20 '13 at 3:57

2 Answers 2

up vote 1 down vote accepted
+100

For (a):

For each $\newcommand\abs[1]{\left\lvert#1\right\rvert}a>0$, we'd prove that $$\lim_{x\to+\infty}\int_a^\infty xF(xt)\cos tdt=0$$ (as Macavity has suggested, the improper integral converges out of Dirichlet's test).

Fix $x>0$, take arbitrary $A>a$, we have (by mean value theorem) $$\int_a^AF(xt)\cos tdt=F(ax)\int_a^c\cos tdt+F(Ax)\int_c^A\cos tdt$$ where $c\in[a,A]$.

Therefore $$\abs{\int_a^AF(xt)\cos tdt}\le 2F(ax)\int_{-\pi/2}^{\pi/2}\cos tdt$$ for all $A>a$, thus $$\int_a^\infty F(xt)\cos tdt=o\left(\frac1x\right)\qquad x\to+\infty$$


For (b):

We need to show that $$\lim_{x\to+\infty}x\int_0^{\pi/2}(F(xu)-G(xu))\cos udu=0\tag{*}$$ given that $$\lim_{n\to\infty}n\int_0^{\pi/2}(F(nu)-G(nu))\cos udu=0\tag1$$ (for the virtue of (a), we could replace $\int_0^\infty$ by $\int_0^{\pi/2}$)

Suppose $n\le x<n+1$, we write $$x(F(xu)-G(xu))=\frac xnn(F(nu)-G(nu))-x(F(nu)-F(xu))+x(G(nu)-G(xu))\tag2$$

By (*), we have $$\lim_{x\to+\infty}\frac xn\cdot n\int_0^{\pi/2}(F(nu)-G(nu))\cos udu=0\tag3$$

The second term could be split into two parts $$0\le x(F(nu)-F(xu))=(x-n)F(nu)+(nF(nu)-xF(xu))\le F(nu)+(nF(nu)-xF(xu))$$

Since $zF(z)\to0$ as $z\to+\infty$, we choose $\Delta>0$ such that $F(z)\le1/z$ whenever $z\ge\Delta$, therefore $$\int_0^{\pi/2}F(nu)\cos udu=\int_0^{\Delta/n}+\int_{\Delta/n}^{\pi/2}$$ where $$\int_0^{\Delta/n}\le F(0)\int_0^{\Delta/n}\cos udu\to0$$ as $x\to+\infty$ and $$\int_{\Delta/n}^{\pi/2}\le\frac1n\int_{\Delta/n}^{\pi/2}\frac{\cos u}udu\le\frac1n\int_{\Delta/n}^{\pi/2}\frac{du}u=O\left(\frac{\ln n}n\right)\to0$$

Rewrite $$\int_0^{\pi/2}(nF(nu)-xF(xu))\cos udu=\int_0^{n\pi/2}F(v)\left(\cos\frac vn-\cos\frac vx\right)dv-\int_{n\pi/2}^{x\pi/2}F(v)\cos\frac vxdv$$

Note that $$0\le-\int_0^{n\pi/2}\le 2F(0)\int_0^{n\pi/2}\sin\frac12\left(\frac vn-\frac vx\right)=O\left(\frac1x\right)$$

and $$\int_{n\pi/2}^{x\pi/2}\le\frac{(x-n)\pi}2F(n\pi/2)\to0$$

Hence $$\int_0^{\pi/2}x(F(nu)-F(xu))\cos udu\to0\tag4$$

Similarly, $$\int_0^{\pi/2}x(F(nu)-F(xu))\cos udu\to0\tag5$$

(*) follows from (2),(3),(4),(5).

share|improve this answer
    
Thank you very much.it's very nice –  math110 May 4 '13 at 17:24

For (1):
Given $F(x), G(x) \ge 0$ and $ \displaystyle \lim_{x\to \infty} {x \left(F(x)+G(x)\right)} = 0 \implies \displaystyle \lim_{x\to \infty} {x F(x)} = 0 \implies \displaystyle \lim_{x\to \infty} {F(x)} = 0$.

Also as $\displaystyle \int_{\epsilon}^z {\cos(t) dt} = \sin(z) - \sin(\epsilon)$ is bounded $\forall z >0 $, we have $\displaystyle \int_{\epsilon}^{\infty} {F(xt) \cdot \cos(t) dt}$ is convergent by the Dirichlet test for any given $x > 0$.

Given that the improper integral converges, $\displaystyle \lim_{x\to \infty} {x F(x)} = 0 \implies \lim_{x \to \infty} {{x F(xt) \cos(t)}} = 0 \quad \forall t >0 \implies \lim_{x \to \infty} {\int_{\epsilon}^{\infty} {x F(xt) \cos(t) dt}} = 0 $. This proves (1).


For (2): I assume we are given $\displaystyle\lim_{n\to\infty}\displaystyle\int_{0}^{\infty}\left(F(t)-G(t)\right)\cdot \cos\left(\dfrac{t}{n}\right)dt=0$ and need to prove the result. This seems easy using $x = \dfrac{1}{n}$, unless I miss something.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.